The Influence of Implementation Religious Study on Students’ Religious Behaviour at Senior High Schools Under Religious Foundation in Kupang East Nusa Tenggara - AM Wibowo (Analisa: Journal of Social Science and Religion, 2012)
This research aims to measure the effect of implementation of religious education at the high school under the religious foundations toward religious behavior student in Kupang, East Nusa Tenggara Province. There are five aspect of behaviour that measured include religiosity, honesty, tolerance, love peace and social concerns. Formulation of the problems in this study are (1) are  there any effect of the implementation of religious education for student of religious behavior (2) How is the implementation of religious education as ap- plied to schools under the Religious foundations. (3) how the implementation of the ideal model of religious education at the high school under thereligious foundations. By using the mixed methods  analysis this research found three findings: (1) there is  influence of religion on the behavior of  the implementation of religious education  for learners. (2) religious education at high school under the Religious foundations in Kupang East Nusa Tenggara have implemented five aspects measured in the subjects of religious education. (3) there are three models of a good education: an evaluation of  the  cognitive,  affective and psychomotor, strengthening the practice, and establising communication with inte- gral outsiders .